IDENTIFIKASI TIPOLOGI JALUR PEJALAN KAKI DI KORIDOR JALAN BANDUNG – CIREBON DESA TANJUNGSARI - Kusumawati, Shinta; Nurdiana, Deden; Anisarida, An An (Departement of Civil Engineering, Universitas Winaya Mukti, 2024)
Pedestrian paths or pedestrian paths are facilities that must exist in a city. Pedestrian paths generally function to facilitate pedestrian movement from one place to another easily, smoothly, safely, comfortably and independently. Pedestrian paths are created so that road users, especially pedestrians, can avoid accidents and can enjoy walking activities safely, relaxed and comfortably without having to worry about vehicles crossing them. The unavailability of pedestrian paths on the Jalan Bandung - Cirebon corridor in Tanjungsari Village, Tanjungsari District, Sumedang Regency has caused various problems related to pedestrian safety with many traffic accidents occurring on this route. As a first step in creating a concept plan for pedestrian routes in the Jalan Bandung - Cirebon corridor, it is necessary to identify the typology of pedestrian routes using an overlay analysis method between the land cover map and the spatial pattern map. The study findings in the form of segments will become a land plan for planning pedestrian paths that comply with safety and comfort standards. The results of the analysis state that there are 3 (three) segments that can be used as pedestrian path plans, namely road segment 1 (one) in the trade and services zone in the south with a segment length of 450 meters, road segment 2 (two) in the mixed zone with segment length of 476 meters and segment 3 (three) in the trade and services zone in the north with a segment length of 374 meters, which will be the basis for determining further analysis.